Does Competence Improve The Factors That Affect Good Governance? - Sally Edinov (Information Technology and Science (ITScience), 2022)
Good governance is the most prominent issue in the management of public administration today. The purpose of this study is to investigate the impact of the government's internal control system and fixed asset administration on good governance, with competence serving as a moderating variable. This study was carried out at the work unit of the Directorate General of Natural Resources and Ecosystem Conservation of the Ministry of Environment and Forestry, with a questionnaire distributed to 218 of a total of 225 respondents and data analyzed using smart pls. The findings revealed that the government's internal control system and fixed asset administration had a direct positive effect on improving good governance, but the state apparatus's competence was unable to moderate this relationship. It is clear that the competence of the state apparatus is very similar and that there is no competence gap. Theoretically, this research contributes to the advancement of knowledge, particularly in the public sector accounting sector, and practically, it can be used as material for Ministry-level decision making.